Penerapan Gamifikasi dalam Pembelajaran Menelaah Struktur dan Kebahasaan Teks Berita melalui Platform Genial.Ly Kelas VII di SMPN 1 Telaga - Habibie, Nur Ainsyah; Sartika, Eka; Salam, Salam (Ideas Publishing, 2025)
This study was conducted to address the challenges of enhancing student motivation and engagement in news text analysis learning at SMPN 1 Telaga by utilizing gamification through the Genial.ly platform. The study describes the implementation of gamification in news text analysis learning using the Genial.ly platform in class VII at SMPN 1 Telaga, as well as students' responses to this approach. The method used is qualitative descriptive, with data obtained from observation, interviews, and documentation. The results show that 85.71% of students achieved learning mastery. The implementation of interactive quizzes and a points system successfully created a dynamic learning environment, improving student motivation, participation, and understanding. Although there were technical challenges, the implementation was effective in increasing engagement. Adjustments to the method based on student feedback are necessary for more optimal learning outcomes in the future.